AB0169 Evaluation of frequency and type of physical therapy in more than 3400 patients with systemic sclerosis. (15th June 2017) - Belz, D; Moinzadeh, P; Blank, N; Siegert, E; Henes, J; Worm, M; Sunderkoetter, C; Schmalzing, M; Kreuter, A; Gunther, C; Susok, L; Zeidler, G; et al.
Abstract : Background: Systemic sclerosis (SSc) is a chronic fibrosing autoimmune disease which leads to severe musculoskeletal dysfunction, disability and contractures. Little is known on the type and extent of physical therapy (PT) prescribed to SSc patients in daily practice. Objectives: To determine the type and frequency of PT received by SSc patients. Methods: The data of 3430 clinically well defined SSc patients registered in the database of the German Network for Systemic Sclerosis were analyzed using SPSS. Results: 48, 5% (1662/3430) of the patients were treated with PT. The most frequently used form of PT was lymphatic drainage (23, 6%/876), followed by physical exercise therapy (22%/817) and paraffin wax bath (10, 5%/389). About half of the patients (46, 9%) received two or three different forms of PT simultaneously. The prescription of PT did not correlate with the SSc subtype, as 49, 5% (503/1016) of dcSSc patients, 50, 3% (850/1689) of lcSSc patients and 45, 7% (143/313) of SSc-Overlap patients received PT. PT was significantly more often prescribed to patients with pulmonary fibrosis in 51, 1% (617/1208), synovitis in 61, 6% (299/485) and CK elevation in 61, 1% (174/285) (p=0, 001–0, 029). PT did not correlate with the extent of skin fibrosis as measured by mRSS. Interestingly, patients with joint contractures (45, 5%) (388/853) or tendon friction rubs (40, 6%) (114/281) received significantly less often PT (p=0, 006/ 0, 045). Comparing the prescription of PT during the initial period 2003–2008 (49, 1%; 1937/3942) with the follow up period 2009–2013 (45, 3%; 2217/4899), a significant decrease of PT prescription was observed (p<0, 001). Patterns of PT prescription differed significantly between medical subspecialties (p<0, 005) i.e. rheumatologists, dermatologists. Conclusions: Although SSc is characterized by considerable disability and restriction of motion, less than 50% of patients received PT. The significant decrease in PT prescription during recent years may reflect lack of knowledge how to prescribe PT and more restrictive insurance regulations. Disclosure of Interest: None declared